2018
DOI: 10.4103/aja.aja_2_18
|View full text |Cite
|
Sign up to set email alerts
|

Would male hormonal contraceptives affect cardiovascular risk?

Abstract: The aim of hormonal male contraception is to prevent unintended pregnancies by suppressing spermatogenesis. Hormonal male contraception is based on the principle that exogenous administration of androgens and other hormones such as progestins suppress circulating gonadotropin concentrations, decreasing testicular Leydig cell and Sertoli cell activity and spermatogenesis. In order to achieve more complete suppression of circulating gonadotropins and spermatogenesis, a progestin has been added testosterone to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…That MHC would fulfill many of the aforementioned criteria of an ideal form of contraception and has the support of many men worldwide has leads to significant research and development in this field. Mechanistically, the goal of MHC is the reversible suppression of spermatogenesis to levels consistent with infertility via suppression of testicular Leydig and Sertoli cell function ( 23 ). Through this method, investigations undertaken over the past four decades have shown that MHC can result in suppression of spermatogenesis with subsequent prevention of pregnancy though a commercial product remains unavailable ( 24 ).…”
Section: Basis For the Hormonal Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…That MHC would fulfill many of the aforementioned criteria of an ideal form of contraception and has the support of many men worldwide has leads to significant research and development in this field. Mechanistically, the goal of MHC is the reversible suppression of spermatogenesis to levels consistent with infertility via suppression of testicular Leydig and Sertoli cell function ( 23 ). Through this method, investigations undertaken over the past four decades have shown that MHC can result in suppression of spermatogenesis with subsequent prevention of pregnancy though a commercial product remains unavailable ( 24 ).…”
Section: Basis For the Hormonal Approachmentioning
confidence: 99%
“…However, more randomized-control trials are necessary to determine the full adverse profile of MHC. Moreover, the relatively short length of all the trials to date precludes an adequate assessment of cardiovascular or thromboembolic events related to use ( 23 ).…”
Section: Male Hormonal Contraceptionmentioning
confidence: 99%
“…Questions have been raised regarding the potential metabolic effects of androgen‐progestin combinations used in male hormonal contraception studies and the potential for long‐term consequences on cardiovascular health, 7 including the development of the metabolic syndrome (insulin resistance, hypertension, dyslipidemia, central obesity) or type 2 diabetes 8,9 . Testosterone replacement therapy in hypogonadal men has been shown in some studies to improve insulin sensitivity; the effects of testosterone on metabolic syndrome and type 2 diabetes in men are less consistent 10‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zitzmann reviews some of the data on the potential cardiovascular effects of male hormonal contraceptive regimens that are under development. 8 Finally, An and Gu remind us in their commentary that more studies on the safety of testosterone therapy must be done in Asia, the site of the largest population of men in the world. 9 …”
mentioning
confidence: 99%